Physiological and transcriptome analysis reveals that prohexadione-calcium promotes rice seedling's development under salt stress by regulating antioxidant processes and photosynthesis. - Yao Li; Hang Zhou; Naijie Feng; Dianfeng Zheng; Guohui Ma; Shengjie Feng; Meiling Liu; Minglong Yu; Xixin Huang; Anqi Huang (PLoS ONE, 2023)
Prohexadione-calcium (Pro-Ca) has been proved to play an important role in releasing abiotic stress in plants. However, there is still a lack of research on the mechanism of Pro-Ca alleviating salt stress in rice. To explore the protective effects of Pro-Ca on rice seedlings under salt stress, we investigated the effect of exogenous Pro-Ca on rice seedling under salt stress by conducting the following three treatment experiments: CK (control), S (50 mmol·L-1 NaCl saline solution) and S + Pro-Ca (50 mmol·L-1 NaCl saline solution + 100 mg·L-1 Pro-Ca). The results indicated that Pro-Ca modulated the expression of antioxidant enzyme-related genes (such as SOD2, PXMP2, MPV17, E1.11.1.7). Spraying Pro-Ca under salt stress significantly increased in ascorbate peroxidase, superoxide dismutase, and peroxidase activity by 84.2%, 75.2%, and 3.5% as compared to the salt treatment, as demonstrated by an example of a 24-hour treatment. Malondialdehyde level in Pro-Ca was also dramatically decreased by 5.8%. Moreover, spraying Pro-Ca under salt stress regulated the expression of photosynthesis genes (such as PsbS, PsbD) and chlorophyll metabolism genes (heml, PPD). Compared to salt stress treatment, spraying Pro-Ca under salt stress significantly increased in net photosynthetic rate by 167.2%. In addition, when rice shoots were sprayed with Pro-Ca under salt stress, the Na+ concentration was considerably reduced by 17.1% compared to salt treatment. In conclusion, Pro-Ca regulates antioxidant mechanisms and photosynthesis to aid in the growth of rice seedlings under salt stress.